Proverbs 31-01: why is the woman of valour of Proverbs 31:10-31 so hard to find? - Penny, Samuel (2019)
This dissertation focuses on Proverbs 31:10-31, the poem about the eset hayil, the co-called ‘woman of valour’. Chapter one will use Reception Theory to show how scholarship on Proverbs, especially discussions about the school/royal court or folk/clan origin of Israelite wisdom, has influenced the interpretation of Proverbs, creating a pre-understanding or research paradigm within which researchers think. I will show how specific interpretations of Proverbs 31:10-31 as part of a hermeneutical framework or inspired by a particular social setting have been influenced by this research paradigm. Chapter two will begin with a literary analysis, discussing the structure and content of Proverbs 31:10-31 and translation difficulties. A more focused word study will pick out key words and ideas in the poem, including military, industry, and action language, in an attempt to reconstruct the horizons of expectations (as understood in Reception Theory) of the original author. From this, I will identify specific motifs and images used by the poem, considering how they are used here and whether they are used similarly here as elsewhere in the Hebrew Bible—that is, whether they reaffirm an established literary motif or image, or go against other uses, challenging the horizons of expectation. Chapter three, perhaps the most speculative part of the project, will undertake an intertextual analysis of the poem, in conversation with the book of Ruth. These texts share a number of similarities, including their focus on women who work for the benefit of home and family, who are both identified as an eset hayil and praised in the gates of the city for their documented deeds. This will build up to an analysis of the term eset hayil itself, to determine whether we should change our understanding of the term from a person to something more akin to a title or accolade someone earns. This would transform the overall function of 31:10-31 from advice literature for the male elite to a song of praise.